Barriers to the Implementation of the HIV Universal Test and Treat Strategy in Selected Primary Care Facilities in South Africa's Eastern Cape Province - Onke R. Mnyaka; Sikhumbuzo A. Mabunda; Wezile W. Chitha; Sibusiso C. Nomatshila; Xolelwa Ntlongweni (SAGE Publishing, 2021)
Background: The South African government implemented the Universal Test and Treat (UTT) approach to treating HIV in the second half of 2016. As part of a contribution to the successful implementation of UTT, this study looked at barriers to implementation of UTT emanating from weaknesses of the health system in 2 Community Health Centers in South Africa's Eastern Cape Province. Methods: This was a quantitative cross-sectional design which had both descriptive and analytical components. Convenience sampling was used to select and recruit 2 primary care facilities and 30 nurses. Self-administered questionnaires were used to solicit data from facility managers and nurses. In addition, a record review was used to access 6 months' data for the period 1 October 2017 to 31 March 2018. Data were analyzed using Stata 14.1. Categorical data were presented using frequency and contingency tables. The 95% confidence interval (95% CI) is used for the precision of estimates and the P -value of statistical significance is P  < .05. Results: Facilities were found to have poor leadership and governance; human resource challenges that include shortages, lack of skills and lack of developmental support; poorly resourced service delivery platforms and poor information management. Of the three 90-90-90 targets, health facilities only satisfactorily achieved the second 90 of initiating all who test positive for HIV within a week (93.1% or n = 288/307). Conclusions: This study has been able to identify potential barriers to the implementation of the UTT strategy at the selected facilities including the lack of structured programs in place to monitor performance of healthcare staff, knowledge gaps, and a lack of good clinical governance practices as evidenced by the lack of customized protocols and Standard Operating Procedures.